THE ROLE OF HEALTH POLYTECHNIC OF PALANGKA RAYA AS A LEADING CENTER FOR ADOLESCENT HEALTH IN CENTRAL KALIMANTAN - Dhini, Dhini (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
-